Review and perspectives on Life Cycle Analysis of solar technologies with emphasis on building-integrated solar thermal systems. (March 2015) - Lamnatou, Chr.; Chemisana, D.; Mateus, R.; Almeida, M.G.; Silva, S.M.
Abstract: Building-Integrated (BI) solar thermal are systems which are integrated into the building, are a new tendency in the building sector and they provide multiple advantages in comparison with the Building-Added (BA) solar thermal configurations. The present investigation is a critical review about Life Cycle Analysis (LCA) studies of solar systems. Emphasis is given on the BI solar thermal installations. Studies about BA configurations and systems which produce electrical (or electrical/thermal) energy are also presented in order to provide a more complete overview of the literature. The influence of the BI solar thermal systems on building environmental profile is also examined. Critical issues such as ongoing standardization and environmental indicators are discussed. The results reveal that there is a gap in the field of LCA about real BI solar thermal (and solar thermal/electrical) installations. Thus, there is a need for more LCA studies which examine the BI solar thermal system itself and/or in conjunction with the building. Active systems which could provide energy for the building would be interesting to be studied. Investigations about the influence of the BI solar thermal systems on building life-cycle performance could also provide useful information in the frame of a more sustainable built environment. Highlights: Critical review of 'solar systems for buildings' Life Cycle Analysis (LCA) is conducted. Emphasis is given on Building-Integrated Solar Thermal Systems (BISTS). Building-added systems, Photovoltaic (PV) and PV/Thermal systems are also cited. The results show that there is a gap in the literature in the field of 'BISTS LCA'. The influence of BISTS on building environmental profile is also examined.